Adaptation of oil refineries to make modern fuels. (January 2018) - Gudde, Nicholas J
The drive to improve efficiency and to reduce emissions (including greenhouse gases) from internal-combustion engines has significant ramifications for fuel properties. Deployment of improved engines is aided by the wide availability of well-defined fuels, sometimes with more stringent specification of properties such as the sulphur content and the vaporisation and combustion characteristics (e.g. the octane rating). Fuel regulation has also led to the inclusion of low-carbon fuel components such as ethanol and biodiesel in mainstream road fuels. These trends will probably continue over the next few decades, and so it is important to understand their implications for commercial-scale fuel production and distribution. This paper provides a technical explanation of the linkages between the properties of commercial-scale fuels, the technologies used to make them and the 'landscape' of the fuels industry (e.g. the distribution systems and the interlinked markets for non-fuel products and energy). Industrially relevant examples are used to explain how the refining industry has adapted, and is still adapting, to the changes in the sulphur and volatility specifications, the mandated biocontent and the changes in engine technology. This paper is not intended to make a case for any specific type of fuel but does aim to explain the principles by which refined fuels can be adapted to meet future specifications or to work in conjunction with alternative fuel components. It covers current issues such as the lower sulphur content, the increased biocontent and the emerging theme of higher-octane-number gasoline as a route to a higher engine efficiency.